Influence Of Rain, Malathion, Sunlit And Shaded Habitats On The Duration Of Development And Molecular Identification Of Chrysomya Megacephala (Fabricius) (Diptera: Calliphoridae) In Kelantan, Malaysia - Mahat, Naji Arafat Haji (2010)
Chrysomya megacephala (Fabricius) is the earliest and the most prevalent necrophagous species infesting dead bodies in Malaysia and thus, may provide the best estimate of minimum postmortem interval (PMI). In Malaysia, heavy and/or incessant rain is commonplace occurrence and malathion is the most prevalent poison used for committing suicide. In this research, the independent and combined influences of rain and presence of malathion in whole rabbit carcasses decomposing in sunlit and shaded habitats on oviposition and development of Ch. megacephala were studied over a period of 1-year in Kelantan,